2023
DOI: 10.5851/kosfa.2022.e62
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Genomic DNA Extracted from Pediococcus acidilactici on Porphyromonas gingivalis Lipopolysaccharide-Induced Inflammatory Responses

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box below Article Type Research article Article Title Inhibitory effect of genomic DNA extracted from Pediococcus acidilactici on Porphyromonas gingivalis lipopolysaccharide-induced inflammatory responses Running Title (within 10 words) P. acidilactici gDNA inhibits P. gingivalis LPS-induced inflammatory responses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, the beneficial effects of structural components derived from L. plantarum , such as genomic DNA, have not been widely documented. Although a previous study has reported that genomic DNA of Pediococcus acidilactici suppressed P. gingivalis LPS-induced inflammatory responses ( Choi et al, 2023 ), we investigated the inhibition of genomic DNA derived from L. plantarum on P. gingivalis LPS-induced inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the beneficial effects of structural components derived from L. plantarum , such as genomic DNA, have not been widely documented. Although a previous study has reported that genomic DNA of Pediococcus acidilactici suppressed P. gingivalis LPS-induced inflammatory responses ( Choi et al, 2023 ), we investigated the inhibition of genomic DNA derived from L. plantarum on P. gingivalis LPS-induced inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, as this study was a review of previous research within a relatively limited field, concluding that its results represent global research trends in the field of animal agriculture and food may be difficult; hence, continuous monitoring through additional follow-up studies is warranted. [110], [111], [112], [113], [114], [115], [116] Malt Genomic DNA; inflammation; Pediococcus acidilactici; periodontitis; Porphyromonas gingivalis [106] Meat Gut microbiota; meat; protein digestion; proteolytic enzyme; sous-vide [117] Meat products Authentication; essential oils; lipidomics; liquid chromatography-mass spectrometry; low-salt meat products; low-sodium meat products; meat product; metabolomics; nanoemulsion; natural preservative; natural salt replacers; salt alternatives; salt-modifying; salt reduction [118], [119], [120] Meat water-holding capacity; whey; whey protein; whipping cream; whipping property; yogurt [122], [123], [124], [125], [126], [127], [128], [129], [130], [131], [132], [133],…”
Section: Discussionmentioning
confidence: 99%